Exlibris hf [Helmer Fogedgaard] / Dolatowski. - Dolatowski, Zbigniew (1927-2001) (1961)
Na tle napisu Exlibris monogram hf. Sygn. aut. w obrębie kompoz., pod wyobrażeniem ołówkiem autograf aut. i data.